Advanced immunophenotyping of lymphocyte and monocyte subsets in healthy Australian adults using a novel spectral flow cytometry panel - Davies, Ainsley R.; Kwong, Kristy; Yu, Zhijia; Diamand, Koula E. M.; Li, Fei-Ju; Kannitha, Laurensia; Ali, Sidra A.; Amjadipour, Abolfazl; Padarin, Ann-Maree; Devoy, Michael; Vohra, Harpreet; Miraghazadeh, Bahar; et al. (Frontiers in Immunology, 2025)
IntroductionLymphocytes play pivotal roles in disease pathogenesis and can be used as potential biomarkers for various immunological conditions. Yet, current flow cytometry methods used in clinical settings are often only capable of measuring between four to eight distinct lymphocyte populations. The purpose of our study was to measure many lymphocyte and monocyte populations from a single sample, with the long-term aim of validating our assay for diagnostic use in the Australian regulatory environment.MethodsWe designed and optimised a novel 30-colour lymphocyte immunophenotyping panel tailored for use on a 3-laser (V-B-R) spectral flow cytometer. This panel measures over 50 lymphocyte and monocyte populations.ResultsIn this report we present data derived from 148 healthy individuals.DiscussionThis lays the groundwork for future clinical application of spectral flow cytometry tests and offers a more comprehensive approach to lymphocyte and monocyte analysis with future implications for disease diagnosis and monitoring.